Perkembangan Ekspor Furniture Kayu (Meja) Indonesia ke China Tahun 2025 dalam Perspektif Perdagangan Internasional - Rika Nurjanah; Daspar Daspar (CV. ITTC INDONESIA, 2026)
Indonesia's wooden furniture industry is one of the export-oriented manufacturing sectors that makes a significant contribution to the country's foreign exchange earnings. In 2025, Indonesia's furniture exports showed positive growth despite the dynamics of global trade. China has become one of the most promising export markets due to the rapid growth of household consumption, urbanization, and the property sector. This study aims to analyze the development of Indonesian wooden furniture exports, particularly wooden tables, to China in 2025 from the perspective of international trade using data obtained from the Central Bureau of Statistics (BPS) and the Indonesian Furniture and Handicraft Industry Association (HIMKI). The results indicate that wooden furniture remains the dominant commodity in Indonesia's furniture exports and has significant potential to expand its market penetration in China. Strengthening product competitiveness, maintaining quality standards, and improving export strategies are expected to further enhance the performance of Indonesia's wooden furniture exports in the international market.